Longitudinal Analysis of Strike Activity - Card, David (Journal of Labor Economics, 1988)
This article presents an empirical study of strike activity in a panel of contract negotiations for some 250 firm-and-union pairs. Evidence is presented on two sources of variation in dispute rates: changes in the characteristics of the collective bargaining agreement that affect subsequent strike outcomes and the effects of lagged strikes on the incidence and duration of subsequent disputes. Strike probabilities are significantly affected by the duration and expiration month of the previous agreement. Dispute rates are also increased by the occurrence of a short strike during the previous negotiations and reduced by the occurrence of a long strike.